Etnografi Pemukiman Tradisional Batak Toba: Hubungan Antara Ruang, Identitas, dan Budaya Dalam Pembangunan Berkelanjutan - Naibaho, Zanrison; Simanjuntak, Daniel Harapan Parlindungan; Rulyani, Ayu; Marlina, Murni Eva; Manalu, Donfordtigo; Br Ginting, Berda Nellyaratri (Sosial Budaya, 2025)
This research aims to analyze the relationship between spatial structure, cultural identity, and local values in traditional Batak Toba settlements as the basis for sustainable development based on local wisdom. Using an ethnographic approach through field observations and in-depth interviews, it was found that the spatial layout of the settlement with its configuration of huta, bolon house, sopo, and alaman communal space represents a clan-based social system and Batak Toba traditional cosmology. Space not only functions utilitarianly, but also has symbolic meaning that reflects social relations, spirituality, and collective identity. The use of local materials, the orientation of buildings towards the environment, and the practice of mutual cooperation in house construction indicate that the Batak Toba people have traditionally applied the principles of ecological and social sustainability. The process of modernization and changes in values have the potential to threaten the sustainability of this traditional space, both physically and symbolically. Therefore, the preservation of traditional settlements needs to not only focus on architectural aspects, but also include the revitalization of cultural values as an integral part of an inclusive and contextual sustainable development strategy Keywords:  Toba Batak, ethnography, cultural identity, sustainability, traditional settlements